Relationship between endometritis and oxidative stress in the follicular fluid and luteal function in the buffalo. (24th August 2016) - Behera, BK; Sharma, CG; Singh, SK; Kumar, H; Chaudhari, RK; Mahla, AS; Das, GK; Krishnaswamy, N
Contents: In this study, alteration in the follicular fluid composition and luteal function was investigated in the buffalo with endometritis. Genitalia were classified into cytological and purulent endometritis on the basis of polymorphonuclear cell cut off while non‐endometritis served as control ( n  = 10/group). In the follicular phase, the number of surface follicles was counted, diameter of the largest follicle was measured and the follicular fluid was assayed for total protein, cholesterol, malondialdehyde (MDA), total antioxidant capacity (TAC), oestradiol (E2 ) and progesterone (P4 ). The P4 content of corpus luteum during mid‐luteal phase was estimated by radioimmunoassay. Ovaries from the follicular phase of oestrous cycle showed no significant difference in the total number of surface follicles, size of the largest follicle and volume of follicular fluid in the buffaloes with and without endometritis ( p  > .05). However, the antral fluid of the largest follicle from the genitalia of buffalo with cytological and purulent endometritis showed a significant decrease in the concentration of total protein, cholesterol, TAC and E2 and a significant increase in the concentration of MDA and P4 ( p  < .05). The results indicated that there is an association between endometritis and decreased ovarian function.